Analyze the Implementation of the 2013 Curriculum in the Virtual Biology Learning Process for Teachers at a Madrasah Aliyah - Siti Hajar Nasution; Ika Chastanti (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2022)
Abstract:Implementing virtual learning using technology media is changes. This is a challenge for Biology teachers, especially in implementing the 2013 curriculum. This study analyzed the implementation of the 2013 curriculum in the virtual biology learning process for teachers at a Madrasah Aliyah in Labuhan Batu Regency, North Sumatra. The method used is the descriptive qualitative with subjects in this study were biology teachers who were selected by purposive sampling. Data were collected through interviews and observations. The collected data were then analyzed using the Miles and Huberman model. The results show that the implementation of the 2013 curriculum in the biology learning process during the Covid-19 pandemic has not been maximized. Teachers still experience obstacles in making and implementing RPP activities in online learning. As a result, learning activities are only centered on the teacher. Abstrak:Penggunaan media teknologi dalam pembelajaran berkembang dengan pesat. Hal ini menjadi tantangan bagi guru Biologi khususnya dalam mengimplementasikan kurikulum 2013. Penelitian ini menganalisis implementasi kurikulum 2013 dalam pembelajaran Biologi secara virtual di salah satu Madrasah Aliyah Swasta di Kabupaten Labuhan Batu Sumatera Utara. Metode yang digunakan adalah kualitatif deksriptif dengan subjek penelitian guru Biologi yang dipilih secara purposive sampling. Data dikumpulkan melalui wawancara dan observasi, kemudian dianalisis menggunakan model Miles dan Huberman. Hasil penelitian menunjukkan implementasi kurikulum 2013 dalam proses pembelajaran Biologi di masa pandemi Covid-19 belum maksimal. Guru masih mengalami hambatan dalam membuat dan melaksanakan kegiatan RPP secara daring. Akibatnya, kegiatan pembelajaran hanya terpusat kepada guru.